Pengaruh Cyber Dakwah Terhadap Peningkatan Kesadaran Religius di Era Gen Z - Selviana Oktaviani Oeva; Nurti Budiyanti; Yuriko Indriani Putri; Nadhira Saffa Aulia; Salsabiila Zhafirah Nathania; Fiki Dwi Alfaiga (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Social media dominates today's modern society, especially in generation Z where they cannot be separated from gadgets. As a generation of modern Muslims, we should continue to study and instill the values of Islamic religious teachings by taking advantage of current technological developments, one of which is through the cyber-dakwah method. Nowadays, various da'wah content has been circulating on social media, but it is still not optimal among teenagers like in generation Z. This study aims to see how cyber da'wah influences social media to increase religious awareness in generation Z in the city of Bandung. This study used a quantitative approach with descriptive methods, as well as data collection through surveys with questionnaire research instruments and quota sampling involving 51 participants. The results showed that cyber da'wah had a positive and significant effect on increasing the Z generation's religious awareness through four aspects, namely pursuing, remembering, feeling, and practicing. The findings of this study support previous research that cyber dakwah is an effective strategy to increase the religious awareness of Muslim youth in the Z generation era. in the preaching content.